Comparative effectiveness and safety of sodium-glucose cotransporter 2 inhibitors vs glucagon-like peptide 1 receptor agonists in elderly patients with type 2 diabetes mellitus: a meta-analysis - Wang, Yao; Wu, Haoming; Yang, Jingxian; Ma, Jun; Li, Hongling; He, Xinyu; Xiao, Yibo; Pan, Yan (Frontiers in Endocrinology, 2025)
ObjectiveThis systematic review aimed to evaluate the cardiovascular effectiveness and safety of initiating sodium-glucose cotransporter 2 inhibitors (SGLT2i) in comparison to glucagon-like peptide 1 receptor agonists (GLP-1RA) among elderly patients with diabetes.MethodsA comprehensive search of the PubMed, Embase, and Web of Science databases was conducted up to March 2024. The summary standard mean differences and odds ratios were calculated.ResultsTwelve studies of eleven articles were included in the analysis. Older patients receiving SGLT2i had a greater incidence of euglycemic ketoacidosis (EKA) (OR 1.622, 95% CI 1.276-2.062, p = 0.000) and genitourinary infection (GUI) (OR 3.59, 95% CI 3.31-3.89, p = 0.00) than did those receiving GLP-1RA, and the opposite was true for acute kidney injury (AKI) (OR 0.902, 95% CI 0.854 - 0.952, p = 0.00). However, no significant differences were detected for major adverse cardiovascular events (MACE) (OR 1.04, 95% CI 0.95-1.13, p = 0.386), hospitalization for heart failure (HHF) (OR 0.98 95% CI 0.83-1.16, p = 0.825), myocardial infarction (MI) (OR 1.09, 95% CI 0.94-1.26, p = 0.265), stroke (OR 1.22, 95% CI 1.02-1.45, p = 0.028), total adverse events (AEs), (OR 0.98, 95% CI 0.83-1.16, p = 0.825), serious AEs (OR 1.02, 95% CI 0.94 -1.11, p = 0.594), fractures (OR 1.07, 95% CI 0.92-1.24, p = 0.394) or hypoglycemia (OR 0.95, 95% CI 0.88-1.02, p = 0.141).ConclusionIn conclusion, although SGLT2i increase the risk of EKA and GUI and GLP-1RA decrease the risk of AKI, SGLT2i are at comparable risk of MACE, HHF, MI, stroke, hypoglycemia, and fracture to GLP-1RA.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024518348.